Evidence of low injection efficiency for implanted p-emitters in bipolar 4H-SiC high-voltage diodes - Matthus, Christian; Hürner, Andreas; Erlbacher, Tobias; Bauer, Anton J.; Frey, Lothar (Solid-State Electronics, 2018)
In this study, the influence of the emitter efficiency on the forward current–voltage characteristics, especially the conductivity modulation of bipolar SiC-diodes was analyzed. It was determined that the emitter efficiency of p-emitters formed by ion implantation is significantly lower compared to p-emitters formed by epitaxy. In contrast to comparable studies, experimental approach was arranged that the influence of the quality of the drift-layer or the thickness of the emitter on the conductivity modulation could be excluded for the fabricated bipolar SiC-diodes of this work. Thus, it can be established that the lower emitter injection efficiency is mainly caused by the reduced electron lifetime in p-emitters formed by ion implantation. Therefore, a significant enhancement of the electron lifetime in implanted p-emitters is mandatory for e.g. SiC-MPS-diodes where the functionality of the devices depends significantly on the injection efficiency.